Angiotensin II Induces Vascular Endothelial Dysfunction by Promoting Lipid Peroxidation-Mediated Ferroptosis via CD36 - Qian Zhou; Ying Zhang; Wei Shi; Lu Lu; Jianglan Wei; Jinhan Wang; Hu Zhang; Yuepu Pu; Lihong Yin (Biomolecules)
Angiotensin II (Ang II) is an effective vasoconstriction peptide, a major effector molecule of the renin–angiotensin–aldosterone system (RAAS) and one of the important causes of endothelial dysfunction. Ferroptosis is considered to be involved in the occurrence and development of cardiovascular diseases. This study is dedicated to exploring the role and mechanism of Ang II-induced ferroptosis in HUVECs and to finding molecular targets for vascular endothelial injury and dysfunction during the progression of hypertension. In this study, we found that with the increase in exposure concentration, the intracellular ROS content and apoptosis rate increased significantly, the NO release decreased significantly in the medium- and high-concentration groups and the ET-1 content in the high-concentration group increased significantly. The expression of ZO-1 protein was significantly decreased in the high-concentration group. The expression of p-eNOS, VE-cadherin and Occludin protein showed a dose-dependent downward trend, while the ICAM-1 protein showed an upward trend. Ang II caused lipid metabolism disorders in HUVECs, and the PL–PUFAs associated with ferroptosis were significantly increased. In addition, Ang II promoted a significant increase in intracellular free Fe2+ content and MDA and a significant decrease in GSH content. Furthermore, the expression of GPX4, SLC7A11 and SLC3A2 was down-regulated, the expression of ACSL4, LPCAT3 and ALOX15 was up-regulated, and the ratio of p-cPLA2/cPLA2 was increased. After the intervention of ferroptosis inhibitor Fer-1, the injury and dysfunction of HUVECs induced by Ang II were significantly rescued. Immunofluorescence results showed that the expression of CD36 showed a significant increasing trend and was localized in the cytoplasm. Over-expression of CD36 promoted Ang II-induced ferroptosis and endothelial dysfunction. In conclusion, Ang II induces the injury of HUVECs, decreases vascular diastole and endothelial barrier-related molecules, and increases vascular constriction and adhesion-related molecules, which may be related to CD36 and its mediated lipid peroxidation and ferroptosis signals.